Analisis Buku Panduan Guru Fase A Kelas I Kurikulum Merdeka Mata Pelajaran Pendidikan Pancasila pada Jenjang Sekolah Dasar - Ni Putu Candra Prastya Dewi (STAHN Mpu Kuturan Singaraja, 2022)
This study aims to analyze the teacher's manual for phase A class I Independent Curriculum subjects of Pancasila Education at the elementary school level. The results showed that the learning objectives designed in the teacher's guide book were in accordance with the learning outcomes contained in the Decree of the Head of the Educational Standards, Curriculum and Assessment Agency of the Ministry of Education, Culture, Research, and Technology Number 033/H/KR/2022 concerning Learning Outcomes. In Early Childhood Education, Elementary Education Levels, and Secondary Education Levels in the Independent Curriculum. It's just that in some units it provides development of goals and emphasis on the realm of spiritual attitudes and social attitudes. In addition, in unit V it appears that there is a merger of two elements, namely Pancasila and Bhinneka Tunggal Ika.